Domestic Violence : Methodologies in Dialogue - Cohen, Shuki J.; Raghavan, Chitra (Book collections on Project MUSE., 2013)
"This volume introduces and critiques the various methodologies employed in current research on domestic violence. By discussing different methodologies side by side as they are applied to the same aspect of domestic violence, and by examining diverse populations (including international samples and sexual minorities), the editors provide insight into the political, sociological, and psychological tensions that influence our understanding of domestic violence. In an integrative pedagogical style, they demonstrate how methods, results, and interpretative frames inform current debates in this field, and how such debates further affect researchers' agendas and preferences. Finally, building on these insights, the book provides readers with a broad and balanced approach to selecting the most appropriate methodology for their inquiries, given the wide range of advantages and shortcomings."--